Welfare implications of overlapping ownership with endogenous quality - Changying Li (Journal of Applied Economics, 2023)
In the context of a vertically differentiated duopoly model with endogenous quality choice, we analyzes the welfare effect of overlapping ownership when the market is fully covered. The results show that overlapping ownership, while detrimental for consumer surplus, may increase or decrease social welfare and firms' profits. In particular, when the overlapping ownership structure is such that the lower-quality firm acquires a positive share of the higher-quality firm's profit, an increase in overlapping ownership reduces the lower-quality firm's incentive to compete against its rival, leading to a higher level of industry profit and, therefore, a higher level of overall welfare.
Keywords: 330; consumer surplus; Overlapping ownership; social welfare; vertical differentiation